Research highlights on contributions of mitochondrial DNA microsatellite instability in solid cancers – an overview - Abdul Yusoff; Siti Radzak; Siti Mohd Khair (Contemporary Oncology)
Cancer has been broadly considered a genetic disease involving mutations in nuclear DNA and the mitochondrial genome (mtDNA). Mitochondria are essential bioenergetics and biosynthetic machinery found in most eukaryotic organisms. Thus, failure of their function is crucial for tumourigenesis, tumour cell growth, and metastasis. Mitochondrial dysregulation can occur as a consequence of molecular alterations in mtDNA, such as point mutations, deletions, inversions, microsatellite instability (MSI), and copy number variations. This review article aims to highlight the published research work on alterations in mtDNA, with a particular focus on mitochondrial MSI (mtMSI) in various types of solid cancers. Databases including PubMed, Scopus, and Google Scholar were searched for articles about mtMSI and its link to solid cancer published from 1990 till 2021. In this review, we briefly summarize the knowledge related to possible molecular mechanisms causing mtMSI formation and the available information on mtMSI frequency values in all main solid cancer types. Mutations in the mitochondrial genome are widely believed to have a broad impact across various cancers. Based on the available published data, mtMSI can act as a vital risk factor and a potential marker for cancer progression. Further research is required to unravel the role of mtMSI in tumourigenesis.